Compreensão de gestores de saúde sobre a inteligência emocional - Camila Cassia de Souza Alves (2022)
Emotional Intelligence (EI) is a relatively new construction and has a proposal to expand the traditional concept of intelligence, considering within this domain aspects related to emotions, feelings and cognition. It has been observed, in the health highlights, a highlight of the IE, improving the development of work, more changes and team resources. Health managers fight the challenges related to technical and behavioral aspects. The technical aspects are easier, however, given their complexity, the challenges to human behavior demand a great emotional effort from the manager, mainly because they deal with professionals who provide direct care to a state of physical and mental suffering, requiring technologies from them. and interpersonal. In this context, this work had the general objective of understanding health managers about the construction of the IE. It also presented, as specific objectives, to expand the practical discussion of science with the participants on the role of emotions in organizational environments and their respective impacts; present the speeches about the work activities of the participants and the EI; encourage participants to reflect on their professional practice and EI; report the behaviors of emotionally intelligent people and their effects on work practice. The approval started after the Research Ethics Committee of the Federal University of Minas Gerais. It was a qualitative research with descriptive purposes. The health study was used as a method, having IE as the unit of analysis or construction and, as research participants, ten health managers graduated in courses related to the health area, being these students and/or graduates of the Professional Master's course in Health Services Management at the Federal University of Minas Gerais, enrolled in the years 2018 and 2020. Data collection was carried out through a semi-structured online interview, after signing the Free and Informed Consent Form. The content of the interviews was fully transcribed and analyzed using the content analysis technique proposed by Franco (2008), establishing the following thematic categories: what is EI; emotions present in the work environment and their interference; behaviors of emotionally intelligent people and their effects on the work environment; socioemotional learning. Through data analysis, it is possible to describe the understanding of health managers about EI, being a set of mental capacities related to the perception, understanding and management of emotions in oneself and in others. It was also possible to demonstrate the relevance of EI to health environments and its numerous benefits, such as: providing a more harmonious, healthy environment, favorable to productivity, performance, teamwork, cooperation, communication and humanized care. The results of this research highlighted the importance of investments aimed at socio-emotional learning, whether personal or organizational. Through this study, it was possible to contribute scientifically to the reflection on the IE construct and the expansion of knowledge that can be applied in the daily lives of health managers and organizations. From an academic perspective, it contributed to the expansion of understanding on the subject, in addition to provoking a reflection on the inclusion of subjects related to the development of socio-emotional skills in the curricular matrices of undergraduate courses in the health area. For society, it collaborated with the training of professionals who are more aware of their emotions and how they interfere in interpersonal relationships and customer/patient care. The proposed technical product was the development of training on EI, with the target audience of health managers who participated in this study. The training objectives were: to share scientific knowledge about EI; share practical methods and tools that favor emotional management in healthcare settings; and instruct health managers so that they are able to be influencers and protagonists of emotional well-being in teams.